Voices of Tigray Women on the 2020 Election: The Freedom to Vote - Sintayoh Fissha; Shahid Islam (International Journal of Regional Development, 2022)
Between 1974 to 1991 the Tigray women played a remarkable role in the country’s history. Realizing the unfair gender relations and its implication for socio-economic and political development they joined the armed struggle which led to the inclusion of women in national/regional politics. Subsequently, a normative question of gender norms was clearly defined; political and other public positions that disregarded women slowly diminished. There are still positive questions raised due to the mis-implementation of laws and policies, but Tigray women hoped that the gap can be narrowed as democracy progresses, and when they are able to elect their representatives. While expecting more in the six-round national and regional election of Ethiopia, which was supposed to be in April 2020, the Tigray women had been told due to COVID-19 the sixth-round election has been postponed/canceled for an unlimited period. Tigray women challenged this action, firstly; the decision was without public participation, and secondly; the time when COVID-19 will become harmless was unknown. An informant articulated the danger of the current Ethiopian government; omissions threatened to breach or breached the constitutional order. Consequently, Tigray women resisted the decision saying, “Tigray will vote” following the regional laws as the constitution grants. This paper presents why Tigray women were in favor of having an election unlike a decision made at the federal, which was explained using the warm glow theory. To conduct this study primary and secondary data were collected using snowball sampling that was analyzed by applying qualitative (thematic) analysis. The findings revealed that Tigray women preferred to have an election than canceling, as they deemed it help them to maximize their expected utility and granted them with warm glow pay-off.